2016
DOI: 10.1364/oe.24.022004
|View full text |Cite
|
Sign up to set email alerts
|

Fault-tolerant and finite-error localization for point emitters within the diffraction limit

Abstract: We implement a self-interference technique for determining the separation between two incoherent point sources. This method relies on image inversion interferometry and when used with the appropriate data analytics, it yields an estimate of the separation with finite-error, including the case when the sources overlap completely. The experimental results show that the technique has a good tolerance to noise and misalignment, making it an interesting consideration for high resolution instruments in microscopy or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(65 citation statements)
references
References 22 publications
2
63
0
Order By: Relevance
“…[16] that approaches the QCR bound for sub-Rayleigh separations. Recent experimental work [17][18][19][20] inspired by the above proposals has substantiated the surprising findings of the above papers.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…[16] that approaches the QCR bound for sub-Rayleigh separations. Recent experimental work [17][18][19][20] inspired by the above proposals has substantiated the surprising findings of the above papers.…”
Section: Introductionsupporting
confidence: 54%
“…[39,40] in which the general properties of the device were studied and ref. [17] for an implementation in the context of two-source resolution), which was required in the scheme of ref. [16] Our analysis here can be extended in various directions.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…SPLICE does not correspond exactly, however, to projecting in the Hermite-Gauss basis. The scheme proposed in [150] relies on image inversion interferometry, that is a Mach-Zender interferometric scheme in which image inversion is performed in one of the two arms. The two displaced sources with Gaussian PSFs are sent through the interferometer, and a delay is added on one of the arms to fine-tune the interference.…”
Section: Multiparameter Estimation In Separation Measurementsmentioning
confidence: 99%
“…Recent research, initiated by our group [1][2][3][4][5][6][7], has shown that far-field linear optical methods can significantly improve the resolution of two equally bright incoherent optical point sources with sub-Rayleigh separations [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15], overcoming previously established statistical limits [16][17][18][19]. The rapid experimental demonstrations [12][13][14][15] have heightened the promise of our approach. An open problem, of fundamental interest in optics and monumental importance to astronomy and fluorescence microscopy, is whether these results can be generalized for an arbitrary distribution of incoherent sources.…”
Section: Introductionmentioning
confidence: 99%